(3GdehGgH GddOfjI HGdefM GdeMeOjIs - (3CMeO Hf eMeO Hf CHj HcQ Hf YHO Gdedc GdbJjHj GdeUQj GdbSWdGfj , TgGH GdOjf CHh GdYHGS,J (B923 (3g` s
(3ChdgG (B:s
(3QHfG BJfG ef dOfc QMeI hgjF dfG ef GeQfG QTOG GdMeO ddg GdPi CWdY ai SeGA GdCRd TeS CfhGQ eYGQa GdfHhI GdeMeOjI s
(3BNQgG (B:s
(3hbO aQZJ ef JHjjVg aj NGeS YTQ ef TYHGf GdecQe, SfI JSY h JSYjf h KeGfeGFI , hef JShjOg ai KGfj ThGd , SfI KeGf hJSYjf h KeGfeGFI s
(3HChdgG agQS HGdehVhYGJs
(3hGdeNWhW ebShe Ydi ajdejf hehVhY aj YdHJjfs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B232 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B85s
Keywords: (3GdJGQjNs